Ion concentration-dependence of rat cardiac unitary L-type calcium channel conductance. - Guia, A (2001)
Little is known about the native properties of unitary cardiac L-type calcium currents (i(Ca)) measured with physiological calcium (Ca) ion concentration, and their role in excitation-contraction (E-C) coupling. Our goal was to chart the concentration-dependence of unitary conductance (gamma) to physiological Ca concentration and compare it to barium ion (Ba) conductance in the absence of agonists. In isolated, K-depolarized rat myocytes, i(Ca) amplitudes were measured using cell-attached patches with 2 to 70 mM Ca or 2 to 105 mM Ba in the pipette. At 0 mV, 2 mM of Ca produced 0.12 pA, and 2 mM of Ba produced 0.19 pA unitary currents. Unitary conductance was described by a Langmuir isotherm relationship with a maximum gammaCa of 5.3 +/- 0.2 pS (n = 15), and gammaBa of 15 +/- 1 pS (n = 27). The concentration producing half-maximal gamma, Kd(gamma), was not different between Ca (1.7 +/- 0.3 mM) and Ba (1.9 +/- 0.4 mM). We found that quasi-physiological concentrations of Ca produced currents that were as easily resolvable as those obtained with the traditionally used higher concentrations. This study leads to future work on the molecular basis of E-C coupling with a physiological concentration of Ca ions permeating the Ca channel.